1998
DOI: 10.1001/archpedi.152.10.977
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Saving Algorithm for Children Hospitalized for Status Asthmaticus

Abstract: To test the ability of an assessment-driven algorithm for treatment of pediatric status asthmaticus to reduce length and cost of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 26 publications
1
56
0
Order By: Relevance
“…Previous studies have had relatively small sample sizes, selected cohorts, use of historical control subjects, or ignored the impact of such a program on healthcare costs (8)(9)(10)(11)(12)(13)(14)(15)(16). Some of these studies, but not all, have demonstrated a beneficial effect on healthcare use and asthma knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have had relatively small sample sizes, selected cohorts, use of historical control subjects, or ignored the impact of such a program on healthcare costs (8)(9)(10)(11)(12)(13)(14)(15)(16). Some of these studies, but not all, have demonstrated a beneficial effect on healthcare use and asthma knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, given that these types of hospitals are serving a disproportionately large share of medically complex and low-SES children, these hospitals should prioritize implementation of interventions shown to improve quality of care for children admitted with respiratory illness. Single-center studies have shown clinical pathways improve antimicrobial use 38 and reduce radiation exposure, video-assisted thoracoscopic surgery procedures, and readmission rates in children admitted for pneumonia 9 ; reduce resource utilization, [39][40][41] LOS, 41 and readmissions 8 in children admitted for bronchiolitis; and increase home asthma management teaching 7 and decrease in LOS 5,42 in children admitted for asthma. Larger, multicenter studies are needed to determine if clinical pathways are an effective means of improving quality of care for respiratory illnesses, and if pathways are found to be effective, policies should incentivize large, urban-teaching hospitals to implement pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, clinical pathways have been used as an effective strategy to improve compliance with use of peak flow meters, spacers, and prescribing of controller medications at the time of discharge [57][58][59][60]. Clinical pathways have also been shown to decrease length of stay and, therefore, costs associated with hospitalization.…”
Section: Clinical Pathwaysmentioning
confidence: 99%